2022
DOI: 10.3389/fmolb.2021.789703
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Integrated Analysis of HSF2 Expression, Prognostic Value and Potential Implications for Cancer Immunity

Abstract: Heat shock factor 2 (HSF2), a transcription factor, plays significant roles in corticogenesis and spermatogenesis by regulating various target genes and signaling pathways. However, its expression, clinical significance and correlation with tumor-infiltrating immune cells across cancers have rarely been explored. In the present study, we comprehensively investigated the expression dysregulation and prognostic significance of HSF2, and the relationship with clinicopathological parameters and immune infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…DNA methylation is a form of epigenetic modification that regulates gene expression, and hypermethylation may contribute to the inactivation of tumor suppressor genes [ 49 ]. Hence, the associations between DNA methylation and CD276 expression in different types of cancer were investigated, and the results obtained revealed that the DNA methylation level of CD276 was negatively correlated with CD276 expression in many types of cancer, including BLCA, BRCA, HNSC, KIRP, LUAD, LUSC and TGCT, whereas it was positively correlated with other cancer types, including PCPG.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is a form of epigenetic modification that regulates gene expression, and hypermethylation may contribute to the inactivation of tumor suppressor genes [ 49 ]. Hence, the associations between DNA methylation and CD276 expression in different types of cancer were investigated, and the results obtained revealed that the DNA methylation level of CD276 was negatively correlated with CD276 expression in many types of cancer, including BLCA, BRCA, HNSC, KIRP, LUAD, LUSC and TGCT, whereas it was positively correlated with other cancer types, including PCPG.…”
Section: Resultsmentioning
confidence: 99%
“…As a Heat shock protein, it has been reported to be associated with cellular stress and aging in diverse cells, including mesenchymal stem cells, skeletal muscle, and T cells ( 49 51 ). Through various bioinformatics, it has been related to immune cell infiltration and tumor immune microenvironment across different cancer types ( 52 ). Finally, the autophagy-related gene ATG10 regulated the formation of autophagosomes and participated in the anti-virus immune response ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between the hub gene expression of the COADREAD dataset and the immune-related gene set were calculated using the “corr.test” function of Spearman’s algorithm ( https://rpubs.com/aaronsc32/spearman-rank-correlation ), and the correlation heatmap was drawn. The immune checkpoint genes reported by Chen et al ( 26 ) were used to calculate and plot the correlations between these genes and the hub genes in the COADREAD dataset.…”
Section: Methodsmentioning
confidence: 99%